An ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transverse stacking morphology and a preparation method thereof
By gradually adjusting the pH value in the reactor, an ultra-high nickel quadruple positive electrode material precursor with uniform particle size and transverse lamination morphology was prepared, and the cracks and cracks of the precursor of the large-particle positive electrode material in the prior art are solved. The problem of uneven particle size improves the performance and life of the battery.
Patent Information
- Application Number
- CN202310869776.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-07-17
AI Technical Summary
It is difficult to prepare a large particle size ultra-high nickel ternary/quad-member cathode material precursor, which is prone to cracks and uneven particle size problems, which affects battery performance and life.
Using a method of preparing an ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transverse lamination morphology, the pH value is gradually adjusted in a reactor containing hydroxide seeds to control the reaction conditions to avoid nucleation. The saturation level is too high to achieve particle uniformity.
The crack problem of the precursor of the large-particle-sized positive electrode material is effectively avoided, the uniformity of the particle size is achieved, and the discharge capacity and capacity retention rate of the battery are improved.
Smart Images

Figure CN116835669B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion battery positive electrode materials, and specifically relates to an ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transverse stacking morphology and a preparation method thereof. Background Art
[0002] Ultra-high nickel (nickel molar percentage greater than 85%) nickel-cobalt-manganese / aluminum (ternary) or nickel-cobalt-manganese-aluminum (quaternary) layered positive electrode materials have advantages such as high volume and mass energy density and moderate price. High nickel ternary / quaternary positive electrode materials are widely used in electronic products, outdoor power supplies, electric bicycles, new energy vehicles and other fields. When ultra-high nickel ternary / quaternary positive electrode materials are used in power batteries for new energy vehicles, ultra-high nickel ternary / quaternary positive electrode materials are required to have a larger secondary particle size (D 50 is about 12 microns). Since the particle size of the ternary / quaternary cathode material is inherited from its precursor particle size, a large particle size (D 50 (about 12 microns) ultra-high nickel type ternary / quaternary positive electrode material precursor is essential.
[0003] However, it is currently difficult to prepare large-particle conventional ultra-high nickel type ternary / quaternary positive electrode material precursors using the conventional co-precipitation method, that is, large-particle conventional ultra-high nickel type ternary / quaternary positive electrode material precursors in which the primary flaky particles are perpendicular to the center of the secondary particles and the primary particles show a divergent distribution. In the process of preparing large-particle conventional ultra-high nickel type ternary / quaternary positive electrode material precursors, the large-particle conventional ultra-high nickel type ternary / quaternary positive electrode material precursors are prone to cracks and small particles, which leads to cracks in the corresponding large-particle ultra-high nickel type ternary / quaternary positive electrode materials, and further leads to overburning of the corresponding small-particle ultra-high nickel type ternary / quaternary positive electrode materials, affecting the performance and life of the corresponding batteries. Summary of the invention
[0004] In view of this, the present application provides a method for preparing an ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transverse stacking morphology, which solves the problem that the positive electrode material precursor prepared by the prior art is prone to cracks and uneven particle size.
[0005] The present invention also aims to provide an ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transversely stacked morphology.
[0006] To achieve the above object, the technical solution of the present invention is implemented as follows: a method for preparing an ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transverse stacking morphology, the method comprising the following steps:
[0007] S1, to a reactor containing a mixture of hydroxide seeds with uniform particle size, ammonia water with a concentration of 0.1-1.0 mol / L and a pH value of 12.5-13.0, a quaternary A salt solution, a first liquid alkali solution and a first nitrogen-containing complexing agent are continuously added at a certain feeding rate, and the pH value of the reaction system is gradually reduced to 11.5-12 by adjusting the flow rate of the first liquid alkali solution to 0.1-2.0 L / h, and then the feeding is stopped, and the aging is carried out for 20-120 min, and then the quaternary A salt solution, the first liquid alkali solution and the first nitrogen-containing complexing agent are continuously added, and the flow rate of the first liquid alkali solution is adjusted to 0.1-1.0 L / h, and the pH value of the reaction system is gradually reduced to 10.0-10.5, and then the coprecipitation reaction is stopped to obtain a hydroxide slurry;
[0008] S2, precursor preparation stage: the hydroxide slurry obtained in S1 is washed and dried to obtain an ultra-high nickel quaternary positive electrode material precursor with a transverse stacked morphology and uniform particle size.
[0009] In the above technical solution, further, in S1, the temperature of the coprecipitation reaction is 50-80°C.
[0010] In the above technical scheme, further, in S1, the feed rates of the quaternary A salt solution and the first nitrogen-containing complexing agent are 0.5-3L / h and 0.01-1.5L / h respectively; and the concentration of each metal element in the quaternary A salt solution is 1.0~3.0mol / L; the concentration of the first liquid alkali solution is 2.7~14.0mol / L; the concentration of the first nitrogen-containing complexing agent is 5.0~15.0mol / L.
[0011] In the above technical solution, further, in S1, the reactor used is a 50L reactor. For the 50L reactor, the feed rates of the quaternary A salt solution and the first nitrogen-containing complexing agent are 0.5~3L / h and 0.01~1.5L / h, respectively.
[0012] In the above technical scheme, further, in S1, the quaternary A salt solution is a mixture of inorganic salts or organic salts of nickel, cobalt, manganese and aluminum; the molar ratio of Ni:Co:Mn:Al in the quaternary A salt solution is (0.9~1.0):(0.01~0.05):(0.01~0.04):(0.01~0.02).
[0013] In the above technical scheme, further, in S1, the inorganic salt of nickel, cobalt, manganese and aluminum is sulfate, nitrate or chloride; the organic salt of nickel, cobalt, manganese and aluminum is acetate; the second nitrogen-containing complexing agent is at least one of ammonia water, ammonium sulfite, ammonium bisulfite, ammonium sulfate, ammonium bisulfate, ammonium sulfide, ammonium hydrogen sulfide, ammonium thiosulfate, ammonium chloride or ammonium carbonate.
[0014] In the above technical solution, further, in S1, the first nitrogen-containing complexing agent is at least one of ammonia water, ammonium sulfite, ammonium bisulfite, ammonium sulfate, ammonium bisulfate, ammonium sulfide, ammonium hydrogensulfate, ammonium thiosulfate, ammonium chloride or ammonium carbonate.
[0015] In the above technical solution, further, in S1, the hydroxide seed crystal is obtained specifically by the following method:
[0016] The quaternary B salt solution, the second alkaline solution and the second nitrogen-containing complexing agent are respectively added to a reactor containing an ammonia base solution at a certain feed rate, and the pH value of the reaction system is controlled to be 12.5-13.0 and the concentration of ammonia in the reactor is controlled to be 0.1-1.0 mol / L by adjusting the flow rate of the added materials, and a coprecipitation reaction is carried out to obtain hydroxide seed crystals with uniform particle size.
[0017] In the above technical solution, further, the reactor used is a 50L reactor. For the 50L reactor, the feed rates of the quaternary B salt solution, the second liquid alkali solution and the second nitrogen-containing complexing agent are 0.5~3L / h, 0.1~2L / h and 0.01~1.5L / h respectively.
[0018] In the above technical solution, further, the quaternary B salt solution is a mixture of inorganic salts or organic salts of nickel, cobalt, manganese and aluminum; the molar ratio of Ni:Co:Mn:Al in the quaternary B salt solution is (0.9~1.0):(0.01~0.05):(0.01~0.04):(0.01~0.02).
[0019] In the above technical scheme, further, the inorganic salts of nickel, cobalt, manganese and aluminum are sulfates, nitrates or chlorides; the organic salts of nickel, cobalt, manganese and aluminum are acetates; and the first nitrogen-containing complexing agent is at least one of ammonia water, ammonium sulfite, ammonium bisulfite, ammonium sulfate, ammonium bisulfate, ammonium sulfide, ammonium hydrogensulfide, ammonium thiosulfate, ammonium chloride or ammonium carbonate.
[0020] In the above technical solution, further, the reaction temperature is 30~80°C; and the reaction time is 0.1~5h.
[0021] In the above technical solution, further, the second nitrogen-containing complexing agent is at least one of ammonia water, ammonium sulfite, ammonium bisulfite, ammonium sulfate, ammonium bisulfate, ammonium sulfide, ammonium hydrogensulfate, ammonium thiosulfate, ammonium chloride or ammonium carbonate.
[0022] In the above technical solution, further, the hydroxide seed crystal is spherical.
[0023] The second technical solution of the present invention is achieved in this way: it is prepared by the above-mentioned preparation method.
[0024] In the above technical solution, further, the cathode material precursor has an average particle size of 5-20 μm and a structural formula of Ni x Co y Mn z Al 1-x-y-z (OH)2, wherein 0.9≤x≤1.0, 0.01≤y≤0.05, and 0.01≤z≤0.04.
[0025] Compared with the prior art, by comparing the ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transversely stacked morphology obtained by the method of the present invention with the existing conventional high nickel quaternary positive electrode material precursor in which the primary flaky particles are perpendicular to the center of the secondary particles and the primary particles show a divergent distribution, it is found that since the primary particles of the ultra-high nickel precursor obtained by the present invention are stacked transversely and the transversely stacked primary particles overlap each other, the occurrence of cracks in the large-particle high nickel quaternary positive electrode material precursor is effectively avoided; in addition, the ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transversely stacked morphology obtained by the method of the present invention effectively achieves the purpose of uniform particle size. In addition, the reason for achieving uniform particle size is that the present invention continuously reduces the pH value during the growth process, avoids excessive nucleation supersaturation in the growth stage of the precursor particles, forms new nucleation points outside the large particles, and a large number of new small particles appear, thereby making the particles uniform. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The SEM images of the crystal nuclei prepared in Example 1 of the present invention and the crystal nuclei prepared in Comparative Example 1 (using the same crystal nuclei but different growth modes);
[0027] Figure 2 This is a high-magnification SEM image of the ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transverse stacking morphology prepared in Example 1 of the present invention;
[0028] Figure 3 This is a low-magnification SEM image of the ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transverse stacking morphology prepared in Example 1 of the present invention;
[0029] Figure 4 This is a high-magnification SEM image of the ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transverse stacking morphology prepared in Example 2 of the present invention;
[0030] Figure 5 This is a low-magnification SEM image of the ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transverse stacking morphology prepared in Example 2 of the present invention;
[0031] Figure 6 This is a high-magnification SEM image of the quaternary positive electrode material precursor prepared in Comparative Example 1 of the present invention;
[0032] Figure 7 This is a low-magnification SEM image of the quaternary positive electrode material precursor prepared in Comparative Example 1 of the present invention. Implementation
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] Unless otherwise specified, the chemical reagents used in the embodiments of the present invention were obtained through conventional commercial channels.
[0035] An embodiment of the present invention provides a method for preparing an ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transverse stacking morphology, the method comprising the following steps:
[0036] S1, to a reactor containing a mixture of hydroxide seeds with uniform particle size, ammonia water with a concentration of 0.1-1.0 mol / L and a pH value of 12.5-13.0, a quaternary A salt solution, a first liquid alkali solution and a first nitrogen-containing complexing agent are continuously added at a certain feeding rate, and the pH value of the reaction system is gradually reduced to 11.5-12 by adjusting the flow rate of the first liquid alkali solution to 0.1-2.0 L / h, and then the feeding is stopped, and the aging is carried out for 20-120 min, and then the quaternary A salt solution, the first liquid alkali solution and the first nitrogen-containing complexing agent are continuously added, and the pH value of the reaction system is gradually reduced to 10.0-10.5 by adjusting the flow rate of the first liquid alkali solution to 0.1-1.0 L / h, and then the coprecipitation reaction is stopped, and the temperature of the coprecipitation reaction is 50-80°C to obtain a hydroxide slurry;
[0037] The reactor used is a 50L reactor. For the 50L reactor, the feed rates of the quaternary A salt solution and the first nitrogen-containing complexing agent are 0.5-3L / h and 0.01-1.5L / h, respectively; and the concentration of each metal element in the quaternary A salt solution is 1.0-3.0mol / L; the concentration of the first liquid alkali solution is 2.7-14.0mol / L; the concentration of the first nitrogen-containing complexing agent is 5.0-15.0mol / L; the quaternary A salt solution is a mixed solution of inorganic salts or organic salts of nickel, cobalt, manganese and aluminum; the inorganic salts of nickel, cobalt, manganese and aluminum are sulfates, nitrates or chlorides. ; The organic salts of nickel, cobalt, manganese and aluminum are acetates; the second nitrogen-containing complexing agent is at least one of ammonia water, ammonium sulfite, ammonium bisulfite, ammonium sulfate, ammonium bisulfate, ammonium sulfide, ammonium hydrogen sulfide, ammonium thiosulfate, ammonium chloride or ammonium carbonate; the molar ratio of Ni: Co: Mn: Al in the quaternary A salt solution is (0.9~1.0): (0.01~0.05): (0.01~0.04): (0.01~0.02); the first nitrogen-containing complexing agent is at least one of ammonia water, ammonium sulfite, ammonium bisulfite, ammonium sulfate, ammonium hydrogen sulfate, ammonium sulfide, ammonium hydrogen sulfide, ammonium thiosulfate, ammonium chloride or ammonium carbonate;
[0038] In addition, the hydroxide seed crystal is specifically obtained by the following method:
[0039] The quaternary B salt solution, the second alkaline solution and the second nitrogen-containing complexing agent are added to a reactor containing an ammonia base solution at a certain feed rate, and the pH value of the reaction system is controlled to be 12.5-13.0 and the concentration of ammonia in the reactor is controlled to be 0.1-1.0 mol / L by adjusting the flow rate of the added materials, and a coprecipitation reaction is carried out at 30-80° C. for 0.1-5 h to obtain spherical hydroxide seeds with uniform particle size;
[0040] The reactor used is a 50L reactor. For the 50L reactor, the feed rates of the quaternary B salt solution, the second liquid alkali solution and the second nitrogen-containing complexing agent are 0.5-3L / h, 0.1-2L / h and 0.01-1.5L / h respectively; the quaternary B salt solution is a mixed solution of inorganic salts or organic salts of nickel, cobalt, manganese and aluminum; the inorganic salts of nickel, cobalt, manganese and aluminum are sulfates, nitrates or chlorides; The organic salts of nickel, cobalt, manganese and aluminum are acetates; the second nitrogen-containing complexing agent is at least one of ammonia water, ammonium sulfite, ammonium bisulfite, ammonium sulfate, ammonium bisulfate, ammonium sulfide, ammonium hydrogen sulfide, ammonium thiosulfate, ammonium chloride or ammonium carbonate; the molar ratio of Ni: Co: Mn: Al in the quaternary B salt solution is (0.9-1.0): (0.01-0.05): (0.01-0.04): (0.01-0.02);
[0041] S2, washing and drying the hydroxide slurry obtained in S1 to obtain an ultra-high nickel quaternary positive electrode material precursor with a transverse stacked morphology and uniform particle size; the positive electrode material precursor has an average particle size of 5-20 μm and a structural formula of Ni x Co y Mn z Al 1-x-y-z (OH)2, wherein 0.9≤x≤1.0, 0.01≤y≤0.05, and 0.01≤z≤0.04.
[0042] The following are specific embodiments Example 1
[0043] The Ni with lateral stacking morphology obtained in Example 1 of the present invention 0.96 Co 0.015 Mn 0.015 Al 0.01 The (OH)2 precursor is obtained by the following steps:
[0044] S1, hydroxide seed preparation stage: 1.5mol / L MSO4 (M=Ni, Co, Mn, Al, wherein the molar ratio of Ni: Co: Mn: Al is 0.96: 0.015: 0.015: 0.01) mixed salt solution, 5.0mol / L NaOH solution, 10.0mol / L ammonia complexing agent solution were added into a 50L reactor containing 0.5mol / L ammonia as bottom water at a feed rate of 1.5L / h, 0.9L / h, and 0.06L / h, respectively, the pH value of the coprecipitation reaction system was controlled to be 12.8, the coprecipitation reaction temperature was controlled to be 60°C, the ammonia concentration in the reactor was controlled to be 0.5mol / L, the feed was continued, and the reaction was carried out for 3.0h to obtain Ni 0.96 Co 0.015 Mn 0.015 Al 0.01 (OH)2 seed crystals;
[0045] The Ni 0.96 Co 0.015 Mn 0.015 Al 0.01 The (OH)2 seed crystals were tested by electron microscope scanning. The test results are as follows Figure 1 As shown, by observing Figure 1 It can be seen that the seed crystals obtained in Example 1 are spherical, and the primary flaky particles are perpendicular to the center of the secondary particles, and the primary particles are distributed in a divergent manner;
[0046] S2, precursor growth stage: Ni obtained in S1 0.96 Co 0.015 Mn 0.015 Al 0.01(OH)2 seed crystals were used as the base material, and the concentration of ammonia water in the reactor was adjusted to 0.5 mol / L, and the pH value of the mixed solution in the reactor was 12.8. Then, 1.5 mol / L of MSO4 (M=Ni, Co, Mn, Al, wherein the molar ratio of Ni: Co: Mn: Al was 0.96: 0.015: 0.015: 0.01) mixed salt solution, 5.0 mol / L of NaOH solution, and 10.0 mol / L of ammonia water complexing agent solution were added to the reactor. During the feeding process, the feeding rate of the mixed salt solution was 1.5 L / h, and the feeding rate of the nitrogen water complexing agent solution was 0.06 L / h. The coprecipitation reaction temperature was controlled to 60°C, and the ammonia water concentration in the coprecipitation reactor was controlled to 0.5 mol / L. By adjusting the feeding rate of the NaOH solution to 0.1-2.0 L / h, the pH value of the reaction system was gradually reduced to 11.8, and the feeding was stopped, and the reaction mixture was aged for 60 min. min, then continue to add 1.5mol / L MSO4 and 10.0mol / L ammonia complexing agent solution. During the addition process, the feed rate of the mixed solution is 1.5L / h, the feed rate of the nitrogen complexing agent solution is 0.06L / h, and the temperature is controlled to 60°C. The ammonia concentration in the coprecipitation reactor is controlled to be 0.5mol / L. By adjusting the feed rate of the NaOH solution to 0.1-1.0 L / h, the pH value of the reaction system is gradually reduced to 10.5, and the coprecipitation reaction is stopped to obtain a Ni with a primary particle morphology of horizontal stacking. 0.96 Co 0.015 Mn 0.015 Al 0.01 (OH)2 slurry;
[0047] S3, precursor acquisition stage: washing and drying the slurry obtained in S2 to obtain a Ni 0.96 Co 0.015 Mn 0.015 Al 0.01 (OH)2 precursor.
[0048] The Ni with a lateral stacking morphology of primary particles prepared in Example 1 of the present invention 0.96 Co 0.015 Mn 0.015 Al 0.01 The (OH)2 precursor was tested by electron microscopy at low and high magnifications. The test results are as follows: Figure 2 and Figure 3 As shown, by observing Figure 2 and Figure 3 It can be seen that the Ni with a transversely stacked primary particle morphology prepared in Example 1 of the present invention 0.96 Co 0.015 Mn 0.015 Al 0.01The (OH)2 precursor has no cracks and no small particles. Example 2
[0049] The Ni with lateral stacking morphology obtained in Example 2 of the present invention 0.90 Co 0.05 Mn 0.04 Al 0.01 The (OH)2 precursor is obtained by the following steps:
[0050] S1, hydroxide seed preparation stage: 2.0 mol / L MSO4 (M = Ni, Co, Mn, Al, wherein the molar ratio of Ni: Co: Mn: Al is 0.90: 0.05: 0.04: 0.01) mixed salt solution, 6.0 mol / L NaOH solution, 12.0 mol / L ammonia complexing agent solution were added into a reactor containing 0.8 mol / L ammonia as bottom water at a feed rate of 1.2 L / h, 0.8 L / h, and 0.05 L / h, respectively, the pH value of the coprecipitation reaction system was controlled to be 12.5, the coprecipitation reaction temperature was controlled to be 55 ° C, the ammonia concentration in the reactor was controlled to be 0.8 mol / L, the feed was continued, and the reaction was carried out for 1.0 h to obtain Ni 0.90 Co 0.05 Mn 0.04 Al 0.01 (OH)2 seed crystals.
[0051] S2, precursor growth stage: Ni obtained in S1 0.90 Co 0.05 Mn 0.04 Al 0.01(OH)2 seed crystals are used as the base material, and the concentration of ammonia water in the reactor is adjusted to 0.8 mol / L, and the pH value of the mixed solution in the reactor is 12.5. Then, 2.0 mol / L of MSO4 (M=Ni, Co, Mn, Al, wherein the molar ratio of Ni: Co: Mn: Al is 0.90: 0.05: 0.04: 0.01) mixed salt solution, 6.0 mol / L of NaOH solution, and 12.0 mol / L of ammonia water complexing agent solution are added to the reactor. During the feeding process, the feeding rate of the mixed salt solution is 1.2 L / h, the feeding rate of the nitrogen water complexing agent solution is 0.05 L / h, and the coprecipitation reaction temperature is controlled to 65°C, and the ammonia water concentration in the coprecipitation reactor is controlled to 0.6 mol / L. By adjusting the feeding rate of the NaOH solution to 0.1-2.0 L / h, the pH value of the reaction system is gradually reduced to 11.5, and the feeding is stopped, and the reaction mixture is aged for 20 min. min, then continue to add 2.0 mol / L MSO4, 6.0 mol / L NaOH solution, and 12.0 mol / L ammonia complexing agent solution. During the addition process, the feed rate of the mixed solution is 1.2 L / h, the feed rate of the nitrogen complexing agent solution is 0.05 L / h, and the coprecipitation reaction temperature is controlled to be 65 ° C, and the ammonia concentration in the coprecipitation reactor is controlled to be 0.6 mol / L. By adjusting the feed rate of the NaOH solution to 0.1-1.0 L / h, the pH value of the reaction system is gradually reduced to 10.0, and the coprecipitation reaction is stopped to obtain a Ni with a primary particle morphology of transverse stacking. 0.96 Co 0.015 Mn 0.015 Al 0.01 (OH)2 slurry;
[0052] S3, precursor acquisition stage: washing and drying the slurry obtained in S2 to obtain a Ni 0.90 Co 0.05 Mn 0.04 Al 0.01 (OH)2 precursor.
[0053] The Ni with a lateral stacking morphology of primary particles prepared in Example 2 of the present invention 0.90 Co 0.05 Mn 0.04 Al 0.01 The (OH)2 precursor was tested by electron microscopy at low and high magnifications. The test results are as follows: Figure 4 and Figure 5 As shown, by observing Figure 4 and Figure 5 It can be seen that the Ni with a lateral stacking morphology of primary particles prepared in Example 2 of the present invention 0.90 Co 0.05 Mn 0.04 Al0.01 The (OH)2 precursor has no cracks and no small particles. Example 3
[0054] The Ni with lateral stacking morphology obtained in Example 3 of the present invention 0.95 Co 0.02 Mn 0.02 Al 0.01 The (OH)2 precursor is obtained by the following steps:
[0055] S1, hydroxide seed preparation stage: 2 mol / L MSO4 (M = Ni, Co, Mn, Al, wherein the molar ratio of Ni: Co: Mn: Al is 0.95: 0.02: 0.02: 0.01) mixed salt solution, 4.0 mol / L NaOH solution, 10.0 mol / L ammonia complexing agent solution were added into a 50 L reactor containing 0.3 mol / L ammonia as bottom water at a feed rate of 1.2 L / h, 1.0 L / h, and 0.06 L / h, respectively, the pH value of the coprecipitation reaction system was controlled to be 12.6, the coprecipitation reaction temperature was controlled to be 55 ° C, the ammonia concentration in the reactor was controlled to be 0.3 mol / L, the feed was continued, and the reaction was carried out for 2.0 h to obtain Ni 0.96 Co 0.015 Mn 0.015 Al 0.01 (OH)2 seed crystals;
[0056] S2, precursor growth stage: Ni obtained in S1 0.95 Co 0.02 Mn 0.02 Al 0.01(OH)2 seed crystals are used as the base material, and the concentration of ammonia water in the reactor is adjusted to 0.3 mol / L, and the pH value of the mixed solution in the reactor is 12.6. Then, 2 mol / L of MSO4 (M=Ni, Co, Mn, Al, wherein the molar ratio of Ni: Co: Mn: Al is 0.95: 0.02: 0.02: 0.01) mixed salt solution, 4.0 mol / L of NaOH solution, and 10.0 mol / L of ammonia water complexing agent solution are added to the reactor. During the addition process, the feed rate of the mixed salt solution is 1.2 L / h, the feed rate of the ammonia water complexing agent solution is 0.06 L / h, and the coprecipitation reaction temperature is controlled to 70 ° C, the ammonia water concentration in the coprecipitation reactor is controlled to 0.3 mol / L, and the feed rate of the NaOH solution is adjusted to 0.1~2.0 L / h to make the pH value of the reaction system When the H value gradually decreased to 11.6, the addition was stopped and the aging was continued for 120 minutes. Then, 2.0 mol / L MSO4 and 10.0 mol / L ammonia complexing agent solution were added. During the addition process, the feed rate of the mixed solution was 1.2 L / h, the feed rate of the ammonia complexing agent solution was 0.06 L / h, and the coprecipitation reaction temperature was controlled to 70 ° C. The ammonia concentration in the coprecipitation reactor was controlled to 0.3 mol / L. By adjusting the feed rate of the NaOH solution to 0.1-1.0 L / h, the pH value of the reaction system was gradually reduced to 10.2, and the coprecipitation reaction was stopped to obtain a Ni with a transverse stacking morphology of primary particles. 0.95 Co 0.02 Mn 0.02 Al 0.01 (OH)2 slurry;
[0057] S3, precursor acquisition stage: washing and drying the slurry obtained in S2 to obtain a Ni 0.95 Co 0.02 Mn 0.02 Al 0.01 (OH)2 precursor. Example 4
[0058] The Ni with lateral stacking morphology obtained in Example 4 of the present invention 0.92 Co 0.05 Mn 0.02 Al 0.01 The (OH)2 precursor is obtained by the following steps:
[0059] S1, hydroxide seed preparation stage: 2.0 mol / L MSO4 (M = Ni, Co, Mn, Al, wherein the molar ratio of Ni: Co: Mn: Al is 0.92: 0.05: 0.02: 0.01) mixed salt solution, 5.0 mol / L NaOH solution, 12.0 mol / L ammonia complexing agent solution were added into a reactor containing 0.4 mol / L ammonia as bottom water at a feed rate of 1.2 L / h, 0.9 L / h, and 0.05 L / h, respectively, the pH value of the coprecipitation reaction system was controlled to be 12.8, the coprecipitation reaction temperature was controlled to be 60 ° C, the ammonia concentration in the reactor was controlled to be 0.4 mol / L, the feed was continued, and the reaction was carried out for 3.0 hours to obtain Ni 0.92 Co 0.05 Mn 0.02 Al 0.01 (OH)2 seed crystals;
[0060] S2, precursor growth stage: Ni obtained in S1 0.92 Co 0.05 Mn 0.02 Al 0.01 (OH)2 seed crystals are used as the base material, and the concentration of ammonia water in the reactor is adjusted to 0.4mol / L, and the pH value of the mixed solution in the reactor is 12.8. Then, 2.0mol / L of MSO4 (M=Ni, Co, Mn, Al, wherein the molar ratio of Ni: Co: Mn: Al is 0.90: 0.05: 0.04: 0.01) mixed salt solution and 12.0mol / L of ammonia water complexing agent solution are added to the reactor. During the feeding process, the feeding rate of the mixed salt solution is 1.2L / h, and the feeding rate of the ammonia water complexing agent solution is 0.05L / h. The coprecipitation reaction temperature is controlled to 65°C, and the ammonia water concentration in the coprecipitation reactor is controlled to 0.6mol / L. The feeding rate of the NaOH solution is adjusted to 0.1~1.0 L / h, when the pH value of the reaction system is gradually reduced to 11.8, the addition of materials is stopped, and the aging is carried out for 80 minutes, and then 2.0 mol / L of MSO4 and 12.0 mol / L of ammonia complexing agent solution are added. During the addition process, the feed rate of the mixed solution is 1.2 L / h, the feed rate of the ammonia complexing agent solution is 0.05 L / h, and the coprecipitation reaction temperature is controlled to be 65°C, and the ammonia concentration in the coprecipitation reactor is controlled to be 0.6 mol / L. By adjusting the feed rate of the NaOH solution to 0.1-1.0 L / h, the pH value of the reaction system is gradually reduced to 10.5, and the coprecipitation reaction is stopped to obtain a Ni with a primary particle morphology of lateral stacking. 0.92 Co 0.05 Mn 0.02 Al 0.01 (OH)2 slurry;
[0061] S3, precursor acquisition stage: washing and drying the slurry obtained in S2 to obtain a Ni 0.90 Co 0.05 Mn 0.04 Al 0.01 (OH)2 precursor.
[0062] Comparative Example 1
[0063] The quaternary Ni obtained in Comparative Example 1 0.96 Co 0.015 Mn 0.015 Al 0.01 The (OH)2 precursor is obtained by the following steps:
[0064] S1, hydroxide seed preparation stage: 1.5mol / L MSO4 (M=Ni, Co, Mn, Al, wherein the molar ratio of Ni: Co: Mn: Al is 0.96: 0.015: 0.015: 0.01) mixed salt solution, 5.0mol / L NaOH solution, 10.0mol / L ammonia complexing agent solution were added into a reactor containing 0.5mol / L ammonia as bottom water at a feed rate of 1.5L / h, 0.9L / h, and 0.06L / h, respectively, and the pH value of the coprecipitation reaction system was controlled to be 12.8, the coprecipitation reaction temperature was controlled to be 60°C, and the ammonia concentration in the coprecipitation reactor was controlled to be 0.5mol / L. The feed was continuously added and the reaction was carried out for 3.0h to obtain Ni 0.96 Co 0.015 Mn 0.015 Al 0.01 (OH)2 seed crystals;
[0065] The Ni 0.96 Co 0.015 Mn 0.015 Al 0.01 The (OH)2 seed crystals were tested by electron microscope scanning. The test results are as follows Figure 1 As shown, by observing Figure 1 It can be seen that the seed crystal obtained in this comparative example is spherical, the primary flaky particles are perpendicular to the center of the secondary particles and the primary particles are distributed in a divergent manner.
[0066] S2, precursor growth stage: Ni prepared in S1 0.96 Co 0.015 Mn 0.015 Al 0.01(OH)2 seeds were used as base material, and 1.5 mol / L MSO4 (M = Ni, Co, Mn, wherein the molar ratio of Ni: Co: Mn: Al was 0.96: 0.015: 0.015: 0.01) mixed solution, 5.0 mol / L NaOH solution, and 10.0 mol / L ammonia complexing agent solution were added into a reactor containing 0.5 mol / L ammonia as base water at feed rates of 1.5 L / h, 0.9 L / h, and 0.06 L / h, respectively. The coprecipitation reaction temperature was controlled to be 60 °C, and the ammonia concentration in the coprecipitation reactor was controlled to be 0.5 mol / L. At this time, the pH value of the coprecipitation reaction system was maintained at 11.2, and the feed was continuously added. After 80 hours of reaction, the primary flaky particles were perpendicular to the center of the secondary particles, and the primary particles showed a divergent distribution of Ni 0.96 Co 0.015 Mn 0.015 Al 0.01 (OH)2 slurry;
[0067] S3, precursor acquisition stage: the slurry obtained in S2 is washed and dried to obtain primary flake particles perpendicular to the center of the secondary particles and the primary particles present a divergent distribution Ni 0.96 Co 0.015 Mn 0.015 Al 0.01 (OH)2 precursor.
[0068] The Ni prepared in this comparative example 0.96 Co 0.015 Mn 0.015 Al 0.01 The (OH)2 precursor was tested by electron microscopy at low and high magnifications. The test results are as follows: Figure 6 and Figure 7 As shown, by observing Figure 6 and Figure 7 It can be seen that the Ni obtained in this comparative example 0.96 Co 0.015 Mn 0.015 Al 0.01 The (OH)2 precursor showed cracks and a large number of small particles.
[0069] In summary, by comparing the ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transverse lamination morphology obtained by the method of the present invention with the conventional high nickel quaternary positive electrode material precursor in which the primary flaky particles are perpendicular to the center of the secondary particles and the primary particles are distributed in a divergent manner, it is found that: since the primary particles of the ultra-high nickel precursor obtained by the present invention are transversely stacked, and the transversely stacked primary particles overlap each other, the occurrence of cracks in the large particle size high nickel quaternary positive electrode material precursor is effectively avoided; in addition, the ultra-high nickel quaternary positive electrode material with uniform particle size and transverse lamination morphology prepared by the present invention The equipment used for the material precursor is the equipment used for preparing conventional quaternary positive electrode material precursors, and the process is simple, the output is large, and the process cost is low; in addition, the ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transverse stacking morphology obtained by the method of the present invention effectively achieves the purpose of uniform particle size. In addition, the reason for achieving uniform particle size is that the present invention continuously reduces the pH value during the growth process, avoids excessive nucleation supersaturation during the growth stage of the precursor particles, forms new nucleation points outside the large particles, and a large number of new small particles appear, thereby making the particles uniform. .
[0070] In addition, 5 kg of the Ni 0.96 Co 0.015 Mn 0.015 Al 0.01 The (OH)2 precursor and 4.5 kg of LiOH·H2O were uniformly mixed in a high-speed mixer. The mixed material was placed in a resistance furnace and pre-burned at 400°C for 10 hours, and then calcined at 700°C in an oxygen atmosphere for 15 hours. The calcined material was crushed and sieved to finally obtain an ultra-high nickel quaternary positive electrode material with a transverse stacking morphology.
[0071] The above-mentioned positive electrode materials were assembled into CR2025 button cells, and their electrochemical properties were tested. The results showed that at a current density of 0.1C (17mA / g) and a voltage range of 2.5 to 4.3V, the discharge capacity of the button cell was 225.0mA / g, and the capacity retention rate after 50 cycles at 1C was 98.8%.
[0072] It can be seen that when the precursor obtained by the present invention is used to prepare positive electrode materials and the prepared positive electrode materials are assembled into batteries, the discharge capacity and capacity retention rate of the batteries are effectively improved, thereby further laying a solid foundation for the development of new energy batteries.
[0073] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing an ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transverse stacking morphology, characterized in that: The method comprises the following steps: S1, to a reactor containing a mixture of hydroxide seeds with uniform particle size, ammonia water with a concentration of 0.1-1.0 mol / L and a pH value of 12.5-13.0, continuously adding a quaternary A salt solution, a first liquid alkali solution and a first nitrogen-containing complexing agent, and adjusting the flow rate of the first liquid alkali solution to 0.1-2.0 L / h, so that the pH value of the reaction system is gradually reduced to 11.5-12, stop adding, and age for 20-120 min, then continue to add a quaternary A salt solution, a first liquid alkali solution and a first nitrogen-containing complexing agent, and adjust the flow rate of the first liquid alkali solution to 0.1-1.0 L / h, so that the pH value of the reaction system is gradually reduced to 10.0-10.5, stop the coprecipitation reaction, and obtain a hydroxide slurry; S2, washing and drying the hydroxide slurry obtained in S1 to obtain an ultra-high nickel quaternary positive electrode material precursor with a transverse stacked morphology and uniform particle size; The quaternary A salt solution is a mixture of inorganic salts or organic salts of nickel, cobalt, manganese and aluminum, and the molar ratio of Ni:Co:Mn:Al in the quaternary A salt solution is (0.9-1.0):(0.01-0.05):(0.01-0.04):(0.01-0.02); The hydroxide seed crystals are specifically obtained by the following method: The quaternary B salt solution, the second alkaline solution and the second nitrogen-containing complexing agent are added to a reactor containing an ammonia base solution at a certain feed rate, and the pH value of the reaction system is controlled to be 12.5-13.0 and the concentration of ammonia in the reactor is controlled to be 0.1-1.0 mol / L by adjusting the flow rate of the added materials, and a coprecipitation reaction is performed to obtain hydroxide seed crystals with uniform particle size; The quaternary B salt solution is a mixture of inorganic salts or organic salts of nickel, cobalt, manganese and aluminum, and the molar ratio of Ni:Co:Mn:Al in the quaternary B salt solution is (0.9~1.0):(0.01~0.05):(0.01~0.04):(0.01~0.02).
2. The method for preparing a precursor of an ultra-high nickel quaternary positive electrode material with uniform particle size and transverse stacking morphology according to claim 1, characterized in that: In S1, the temperature of the coprecipitation reaction is 50-80°C.
3. The method for preparing a precursor of an ultra-high nickel quaternary positive electrode material with uniform particle size and transverse lamination morphology according to claim 2, characterized in that: In S1, the concentration of each metal element in the quaternary A salt solution is 1.0-3.0 mol / L; the concentration of the first liquid alkali solution is 2.7-14.0 mol / L; and the concentration of the first nitrogen-containing complexing agent is 5.0-15.0 mol / L.
4. The method for preparing a precursor of an ultra-high nickel quaternary positive electrode material with uniform particle size and transversely stacked morphology according to claim 3, characterized in that: In S1, the reactor used is a 50 L reactor. For the 50 L reactor, the feed rates of the quaternary A salt solution and the first nitrogen-containing complexing agent are 0.5-3 L / h and 0.01-1.5 L / h, respectively.
5. The method for preparing a super-high nickel quaternary positive electrode material precursor with uniform particle size and transverse stacking morphology according to claim 1, characterized in that: The reactor used is a 50L reactor. For the 50L reactor, the feed rates of the quaternary B salt solution, the second liquid alkali solution and the second nitrogen-containing complexing agent are 0.5-3L / h, 0.1-2L / h and 0.01-1.5L / h respectively.
6. The method for preparing a precursor of an ultra-high nickel quaternary positive electrode material with uniform particle size and transverse lamination morphology according to claim 1, characterized in that: The reaction temperature is 30-80° C.; the reaction time is 0.1-5 h.
7. An ultra-high nickel quaternary positive electrode material precursor with uniform particle size and transversely stacked morphology, characterized in that: The cathode material precursor is prepared by the preparation method according to any one of claims 1 to 6; the average particle size of the cathode material precursor is 5 to 20 μm, and the structural formula is Ni x Co y Mn z Al 1-x-y-z (OH)2, wherein 0.9≤x≤1.0, 0.01≤y≤0.05, and 0.01≤z≤0.04.
